2002
DOI: 10.1007/s00439-002-0785-4
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of a locus for autosomal dominant idiopathic scoliosis (IS) to human chromosome 17p11

Abstract: Idiopathic scoliosis (IS) is a spine deformity of unknown etiology. Family studies have suggested that IS may be inherited as a mendelian autosomal dominant trait. We have performed linkage analysis on a three-generation IS Italian family. A positive LOD score value of 3.20 at theta=0.00 was detected with marker D17S799 after a genome-wide scanning. Analysis of six flanking microsatellites confirmed the linkage and haplotype inspection defined an interval of about 20 cM between D17S947 and D17S798. This is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
85
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 20 publications
4
85
0
2
Order By: Relevance
“…9 A similar study in an Italian family mapped a second locus to 17p11.2 (IS2, MIM 607354). 10 Another study reported on the mapping of two loci for IS on chromosome 9q31.2-q34.2 (IS4, MIM 612238) and 17q25.3-qtel (IS5, MIM 612239), the latter by combining information obtained from two unrelated IS families. 11 Recently, a locus for IS and pectus excavatum was found in a single large family on chromosome 18q.…”
Section: Introductionmentioning
confidence: 99%
“…9 A similar study in an Italian family mapped a second locus to 17p11.2 (IS2, MIM 607354). 10 Another study reported on the mapping of two loci for IS on chromosome 9q31.2-q34.2 (IS4, MIM 612238) and 17q25.3-qtel (IS5, MIM 612239), the latter by combining information obtained from two unrelated IS families. 11 Recently, a locus for IS and pectus excavatum was found in a single large family on chromosome 18q.…”
Section: Introductionmentioning
confidence: 99%
“…5 Inoue et al 6 reported AIS concordance rates as 92.3% in monozygotic twins, and 62.5% in dizygotic twins. Recent genome-wide linkage analyses have identified many predisposing loci of AIS, [7][8][9][10][11][12][13][14][15][16] further supporting a role of genetic factor(s) in AIS. Single nucleotide polymorphisms (SNPs) in the genes for estrogen receptor 1 (ESR1), 17 estrogen receptor 2 (ESR2), 18 matrilin 1 (MATN1), 19 melatonin receptor 1B (MTNR1B), 20 and tryptophan hydroxylase 1 (TPH1) 21 are reported to be associated with AIS predisposition.…”
mentioning
confidence: 99%
“…The aetiology remains unclear. Previous studies focused on histological factors such as cartilage, skeleton, joint, nerve and muscle but remain inconclusive [2][3][4][5]. In recent years, several studies have indicated that genetic factors play an important role in IS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These studies also show a high genetic heterogeneity of either autosomal dominant inheritance with a major gene or multifactorial modes of inheritance. Autosomal dominant [3][4][5], X-linked dominant [6] and multifactorial inheritance [1,7,8] are commonly reported. In this study, we investigated 214 IS families recuited in Southwest Hospital (Chongqing, China) by using the genetic epidemiological method and analysed effects of genetic factors and the mode of inheritance through patients' age, IS incidence, familial aggregation and heritability, as well as traits of hereditary diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation